Kinesiology tape counters balance impairment after eccentric exercise - Hosp, S.; Folie, R.; Csapo, R.; Hasler, M.; Nachbauer, W. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Exhaustive exercise has been shown to impair balance ability, thus increasing the risk of knee injury in sports (Changela et al., 2012). Even though the use of Kinesiology tape (KT) has lately gained popularity within the sporting community for injury prevention, there is a paucity of evidence demonstrating its effectiveness (Williams et al., 2012). Therefore, the aim of this study was to investigate the influence of KT on balance ability after eccentric exercise in healthy men. Methods: Twelve young men (age: 23.3 ± 2.6 years) with no prior history of lower limb injury took part in this study. All participants were invited to two visits separated by one week, to perform the scheduled tests once without the use of KT and once after application of KT at the knee joint. Upon each visit, the ability to maintain balance was assessed in a single-leg stance test using a computerized balance stability test system (Biodex Balance System®) prior to and immediately after an eccentric exercise. The exercise protocol consisted of 30-minute downhill walking on a treadmill at an inclination of 20%. A stability index was calculated and statistically analyzed by repeated-measures ANOVA. Results: Without KT, the stability index increased from 2.5° to 3.0° after downhill walking, which reflects an exercise-related deterioration of balance. Following application of KT, by contrast, the stability index remained almost unchanged (2.5° to 2.6°). The "time × taping" interaction effect was significant (p = 0.049), indicating that the exercise-related change of the stability index differed between the two taping conditions, with the impairment of balance being significantly greater when no KT was used. Discussion: Eccentric exercise resulted in a significant deterioration of balance ability which could be attenuated by usage of KT. Thus, KT applied to the knee joint counteracted the exercise-related decline of balance ability observed when no tape was used. As its elastic material pulls and stretches the skin, KT might increase the sensory feedback from various mechanoreceptors located in the skin, muscle, and joint capsule, thereby improving proprioceptive performance and balance ability (Chang et al., 2010). Since the exercise-related impairment of balance ability represents an important risk factor for knee injuries, application of KT may be a clinically useful tool for injury prevention by enhancing the balance ability of athletes in the fatigued state.